11 Conscious sedation as the default anaesthetic approach for transcatheter aortic valve insertion (TAVI). (28th September 2016) - Bajrangee, A; Coughlan, JJ; Sullivan, V; Tierney, A; Ullah, I; Connor, CO; Flood, R; Murphy, RT; Foley, B; Maree, AO; Crean, PA
Abstract : Aim: TAVI has traditionally been performed under general anaesthetic (GA), as there is no consensus on anaesthetic management. Our default has been to perform TAVI under conscious sedation (CS) for non-surgical access, since the inception of our program. We sought to determine the efficacy, safety and cost savings of this approach. Methods: We reviewed our program at St James's Hospital and Blackrock Clinic, Dublin from commencement in September 2008 to December 2014. Mean EURO II score, 30 day and one year mortality; cerebrovascular complications, vascular and major bleeding complications (drop in Hb > 2 g/dl), acute kidney injury (AKI) and length of stay were compared between GA and CS groups. Results: TAVI was undertaken on 145 patients. 13 patients had a primary surgical access and were excluded from our analysis. 132 patients underwent TAVI implantation via a non-surgical approach; 27/132 (20%) under GA and 105/132 (80%) under CS. Table 1 highlights the demographic data and procedural outcomes. CS was associated with a significantly shorter length of stay and incidence of acute kidney injury. The estimated hospital cost of 1000 euro per night per patient means that the shorter length of stay for CS generated significant cost savings compared to GA. Conclusion: TAVI using conscious sedation is associated with a much shorter post procedural hospital stay, significant cost savings and similar procedural success. Conscious sedation should be the default anaesthetic approach for non-surgical access.